Analysis of Influencer Credibility Mediating the Impact of Content Marketing on Emina’s Purchase Desision - Salma Salsabila Lestari; Syti Sarah Maesaroh; Adam Hermawan (CV. Ulil Albab Corp, 2024)
This study aims to analyze the credibility of influencers mediating the impact of content marketing on purchasing decisions for Emina products. The research method used is associative quantitative, with data collected through questionnaires distributed to 170 respondents who are users of Emina Glossy Stain and have seen review content labeled